The pollen as bioindicator of the genotoxicity of environment - Vasilevskaya Natalia; Sikauluk Anna; Osechinskaya Polina (E3S Web of Conferences, 2023)
In recent years the male gametes of plants are used for biotesting in ecotoxicology. High proportion of sterile pollen is the indicator of environmental pollution and the presence of mutagens, which cause genetic disturbances. The viability of pollen of Gorodkov’s rowan (Sorbus gorodkovii Pojark) and Scots pine (Pinus sylvestris L.) in the vicinity of environmentally hazard enterprises of the Arctic cities of the Murmansk region have been studied. The following parameters were considered: the number of fertile and sterile pollen and their percentage ratio, the sterility index, and palynotoxic effect of the pollution. High content of the abortive pollen of S. gorodkovii (55–65%), the sterility index (2.1–2.4) and the palynotoxic effect (38.2–50%) indicates the mutagenicity and genotoxicity of the emissions of the Murmansk thermal power plants, that leads to the formation of sterile male gametes. High level of sterility of P. sylvestris pollen (42.5–50.7%), the index of sterility (1.4–1.7) and the palynotoxic effect (19.1–29.8%) indicates, that emissions of the mining and processing plant "Apatit" containes the mutagenic chemicals that have a genotoxic effect on the pine male gametophyte. The pollen of plants can be used for bioindication of environment as the indicator of the impact of gametopathogenic factors.